Extreme rainfall events and cooling of sea turtle clutches: Implications in the face of climate warming. Issue 1 (17th December 2020) - Laloë, Jacques‐Olivier; Tedeschi, Jamie N.; Booth, David T.; Bell, Ian; Dunstan, Andy; Reina, Richard D.; Hays, Graeme C.
Abstract: Understanding how climate change impacts species and ecosystems is integral to conservation. When studying impacts of climate change, warming temperatures are a research focus, with much less attention given to extreme weather events and their impacts. Here, we show how localized, extreme rainfall events can have a major impact on a species that is endangered in many parts of its range. We report incubation temperatures from the world's largest green sea turtle rookery, during a breeding season when two extreme rainfall events occurred. Rainfall caused nest temperatures to drop suddenly and the maximum drop in temperature for each rain‐induced cooling averaged 3.6°C ( n  = 79 nests, min = 1.0°C, max = 7.4°C). Since green sea turtles have temperature‐dependent sex determination, with low incubation temperatures producing males, such major rainfall events may have a masculinization effect on primary sex ratios. Therefore, in some cases, extreme rainfall events may provide a "get‐out‐of‐jail‐free card" to avoid complete feminization of turtle populations as climate warming continues. Abstract : We report incubation temperatures from the world's largest green sea turtle rookery, during a breeding season when two extreme rainfall events occurred. Rainfall caused nest temperatures to drop suddenly and the maximum drop in temperature for each rain‐induced cooling averaged 3.6°C ( n  = 79 nests, min = 1.0°C, max = 7.4°C). Since green sea turtles have temperature‐dependent sex determination, with low incubation temperatures producing males, such major rainfall events may have a masculinization effect on primary sex ratios.